1992
DOI: 10.1152/ajpcell.1992.262.2.c405
|View full text |Cite
|
Sign up to set email alerts
|

GTP gamma S-dependent regulation of smooth muscle contractile elements

Abstract: Guanosine 5'-O-(3-thiotriphosphate) (GTP gamma S) increases the sensitivity of the contractile response to activation by Ca2+ in permeabilized tracheal smooth muscle. Increased tension was associated with a proportional increase in myosin light chain phosphorylation. The site of phosphorylation was determined to be serine-19, which corresponds to the site rapidly phosphorylated by myosin light chain kinase. GTP gamma S did not affect the contraction induced by the protein phosphatase inhibitor okadaic acid but… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
63
0

Year Published

1996
1996
2000
2000

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 138 publications
(64 citation statements)
references
References 30 publications
1
63
0
Order By: Relevance
“…Except for Ca 2ϩ -independent MLC kinase (9, 13), we find no documentation that the exogenous addition of kinases to the cytosol of permeabilized smooth muscle directly exerts contractile responses comparable with findings with CAT. Because the inhibition of myosin phosphatase may possibly be the main mechanism of the G-protein-mediating Ca 2ϩ sensitization of smooth muscle contraction (1,9,24,25,27), the CAT-induced contraction of G-protein-uncoupled smooth muscle permeabilized by Triton X-100 (Fig. 1) may be also mediated by the inhibition of myosin phosphatase.…”
Section: Rho-kinase and Smooth Muscle Contraction 12258mentioning
confidence: 99%
See 2 more Smart Citations
“…Except for Ca 2ϩ -independent MLC kinase (9, 13), we find no documentation that the exogenous addition of kinases to the cytosol of permeabilized smooth muscle directly exerts contractile responses comparable with findings with CAT. Because the inhibition of myosin phosphatase may possibly be the main mechanism of the G-protein-mediating Ca 2ϩ sensitization of smooth muscle contraction (1,9,24,25,27), the CAT-induced contraction of G-protein-uncoupled smooth muscle permeabilized by Triton X-100 (Fig. 1) may be also mediated by the inhibition of myosin phosphatase.…”
Section: Rho-kinase and Smooth Muscle Contraction 12258mentioning
confidence: 99%
“…However, as the use of Ca 2ϩ indicator revealed that the force/ Ca 2ϩ ratio is variable, the Ca 2ϩ -CaM-dependent MLC kinase pathway cannot solely account for the mechanisms of agonistor GTP␥S-induced increases in the force/Ca 2ϩ ratio, so-called Ca 2ϩ sensitization (1,(5)(6)(7)(8)(9). Thus, an additional mechanism that can regulate Ca 2ϩ sensitization of smooth muscle has been proposed.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Myosin phosphorylation is the ®nal determinant of smooth muscle contraction; [Ca 2+ ] i sensitivity of tension is correlated to [Ca 2+ ] i sensitivity of myosin light chain (MLC 20 ) phosphorylation (Ikebe et al, 1988;Rembold, 1990). Myosin phosphorylation is modulated by MLC 20 -kinase and MLC 20 -phosphatase which are under the control of G-proteins (Kitazawa et al, 1991;Kubota et al, 1992). Pertussis toxin (PTX), an inhibitor of G i/o -proteins, reduces the vasoconstrictor response to aadrenoceptor agonists in the rat tail artery (Li & Triggle, 1993).…”
Section: Introductionmentioning
confidence: 99%
“…Although in tracellular Ca^"^ levels are the main regulator of MLCK activity, other mechanisms can alter the state of Ser^^ phosphorylation levels while Ca^^ levels remain con stant. In particular, it has been suggested that signals deriving from the Rho family of small GTP-binding pro teins lead to inhibition of myosin phosphatase activity, thus altering Ser'^ phosphorylation levels (Fujiwara et al 1989;Kitazawa et al 1989Kitazawa et al , 1991Kubota et al 1992;Noda et al 1995;Gong et al 1996). Kimura et al (1996) have shown recently that a Rho-binding Ser/Thr kinase (Rho-kinase) can phosphorylate and thereby inhibit the activity of a myosin phosphatase in vitro.…”
mentioning
confidence: 99%